Reductibilite des systems produits-croises a valeurs dans des groupes compacts - Krikorian Raphael (Paris Societie Mathematique de France, 1999)
In this book it has been studied the problem of reducibility (conjugacy to constants) of quasi-periodic skew-product systems with values in compact semisimple groups, as well as the existence of Floquet type solutions for linear differential quasi-period
Keywords: Semisimple groups